Strategic Leadership and Employee Performance: Unraveling the Mediating Role of Managerial Competence - Nandang Nandang; Disman Disman; Janah Sojanah; Hady Siti Hadijah (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the effect of strategic leadership on employee performance, with managerial competence as a mediator. A quantitative survey method was employed in this study, involving 65 respondents, all employees of PT. Almeira Putri Rahmat Karawang, using a saturated sampling technique. The research instrument was developed based on indicators for each variable and measured using a Likert scale. Data analysis was conducted using a PLS-based SEM approach. The results of the outer model test indicate that all indicators are convergently valid, and the constructs used have met the criteria for reliability and discriminant validity. The R-squared value indicates that employee performance can be explained by the independent variables by 58.4%, while managerial competence explains 17.7%. The results of the hypothesis testing indicate that strategic leadership has a positive and significant effect on employee performance, strategic leadership has a positive and significant effect on managerial competence, and managerial competence also has a significant effect on employee performance. Managerial competence significantly mediates the relationship between strategic leadership and employee performance. These findings emphasize the importance of managerial competency in strengthening the influence of strategic leadership on improving employee performance.